The Changing Political Economies of Small West European Countries - Becker, Uwe; Noordegraaf-Eelens, Liesbeth; Tsipouri, Lena; Stenius, Vanja (Changing Welfare States, 2011)
This important volume sheds light on a group of smaller European countries, often overlooked in economic discussions, that share a high degree of corporatism-Austria, Belgium, Denmark, Finland, the Netherlands, Norway, Sweden, and Switzerland. The contributors to this book investigate the various trajectories of these countries' economies, with particular consideration devoted to their welfare systems, corporate governance, and labor markets from the early 1990s to the economic crisis of 2008. Importantly, The Changing Political Economies of Small West European Countries also investigates various nations as possible socio-economic models for pan-European capitalism.